Epidemiology, pathogenesis and management of atrial fibrillation in athletes - a narrative review - Zabierowski, Jan; Tomasiewicz, Anna; Pachana, Maciej; Kukuła, Piotr; Piersiak, Marcin; Sawczuk, Hubert; Marschollek, Julia; Ziomek, Maciej (Quality in Sport, 2025)
Background:Atrial fibrillation (AF) is the most common cardiac arrhythmia, affecting millions worldwide. While moderate physical activity is known to reduce AF risk, endurance athletes, particularly males, appear to have a higher prevalence of AF. The relationship between physical activity and AF follows a U-shaped curve, where both sedentary lifestyles and extreme-levels of physical activity increase the risk. Understanding the pathophysiology, risk factors, and management of AF in athletes is crucial for optimizing both cardiovascular health and athletic performance. Aim of the work:This study aims to review current literature on AF in athletes, focusing on its prevalence, pathophysiology, risk factors, gender differences, clinical significance, and management strategies. It also seeks to identify gaps in research and suggest future directions for improving prevention and treatment in this population. Materials and methods: A thorough literature review was conducted using databases such as PubMed and Google Scholar, covering studies from the last 20 years. Keywords included "atrial fibrillation," "athletes," "endurance sports," and "exercise-induced AF." Studies were selected based on relevance, methodology, and sample size. Results: Findings suggest that AF prevalence is significantly higher in endurance athletes, particularly in middle-aged men with long-term high-intensity training. Key contributing factors include atrial remodeling, inflammation, fibrosis and autonomic nervous system imbalance. While male athletes appear to be at greater risk, evidence in female athletes remains limited and inconclusive. Management strategies emphasize risk factor modification, individualized treatment plans, careful use of medications and ablation therapy. Exercise reduction as a preventive strategy remains debated.